DIGITAL LITERACY SKILLS FOR LEARNING IN THE NEW NORMAL - Yuangsoi, Pichayapa; Wannakhao, Chartchavalit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
Thailand in the 21st century has embraced education as a crucial means to drive economic and social progress. The Smart Thailand 2020 policy stands as a significant initiative, aiming to offer equal opportunities ensuring that all citizens can benefit from essential infrastructure and nurturing personnel to be smart ICT users in managing 21st-century teaching and learning. This policy prioritizes the development of 21st-century learning skills for learners, essential for lifelong learning, encompassing the 3Rs and 7Cs skills. Thailand has also adopted widely used technology trends, new learning models, and digital literacy to equip learners with the skills needed for self-directed learning, thereby enhancing their digital intelligence. This proficiency would enable learners to adapt to the digital age, social media, and the ‘new normal’ way of life, and effectively integrate into society.